BAITUL ARQAM AS A STRATEGIC CHARACTER EDUCATION MODEL IN DEVELOPING AL-ISLAM AND MUHAMMADIYAH VALUES AMONG STUDENTS - Rohmanur Mala; Tarso Tarso; Siti Atwano Pisriwati; Deny Hadi Siswanto (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The Baitul Arqam program, held at SMA Muhammadiyah Mlati on March 19-20, 2025, aimed to strengthen Islamic identity and build the moral integrity of the participants. The program involved various educational activities, such as discussions on Muhammadiyah ideology, worship training, forums on Islamic values, and reflective activities. It focused not only on theory but also on spiritual experiences that heightened religious awareness. The program was conducted in three main stages: preparation, implementation, and evaluation. The methods used included lectures, role-playing simulations, and discussions. The results of the implementation showed success in motivating participants to delve deeper into Muhammadiyah values, with high enthusiasm throughout the event. Participants also expressed great benefits in preparing themselves to become better Muhammadiyah cadres. Evaluation was carried out using a non-test approach, encompassing cognitive, affective, and psychomotor aspects. The success of this activity highlights the importance of careful planning and good coordination in supporting the strengthening of character and religious understanding among students. This program is expected to be held regularly to prepare future generations who are more committed to the values of the organization